A Comparative Study of Islamic Astronomy and Jurisprudence on the Qibla Direction of Historical Mosques in Cirebon Indonesia - Kusdiyana Kusdiyana; Samsudin Samsudin; Muhammad Buchori; Roqiyul Ma’arif Syam (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
Determining the correct Qibla direction is of utmost importance for Muslims. However, it is ironic that many people are indifferent to the accuracy of the Qibla direction in local mosques, often relying on religious figures without consulting experts in the field. This negligence often results in inaccurate Qibla directions, especially in historical mosques that still stand today. This study examines several historical mosques in Cirebon, Indonesia, including Pesantren Benda Kerep Mosque, Kramat Kalilunyu Mosque, Kramat Kalijaga Mosque, Masjid Merah Panjunan, and Jagabayan Mosque. Among these, only the Pesantren Benda Kerep Mosque has an accurate Qibla direction according to Islamic astronomy (Ilmu Falak). From a jurisprudential perspective (Fiqh), according to the Hanafi, Maliki, and Hanbali schools of thought, the Qibla directions of the historical mosques—except for Jagabayan Mosque—are still acceptable, as they are classified as facing the general direction of the Kaaba (Jihat al-Ka’bah). In contrast, the Pesantren Benda Kerep Mosque's Qibla precisely faces the physical structure of the Kaaba (‘Ain al-Ka’bah). However, Jagabayan Mosque’s Qibla cannot be tolerated as it deviates beyond the acceptable range according to the Hanafi school's concept of jihat sughra. In the Shafi'i school, the strongest opinion is that only the Pesantren Benda Kerep Mosque qualifies as properly aligned with the Qibla, while the others deviate from the correct direction